Chapter 13 Doing Versus Assessing Interactional Competence - Sandlund, Erica (Taylor & Francis, 2019)
This volume features the latest research findings on L2 interactional competence to demonstrate the potential for developing and implementing research-based pedagogy that targets interactional competence (IC) in early instruction in a variety of L2 learning and teaching contexts. Incorporating contributions from both leading and emerging researchers in the area, the book is organized into four sections to provide a systematic account of interactional competence, defined as a set of skills required to　co-construct an effective interaction with a variety of interlocutors in a variety of settings, and advocates for IC to be part of a well-rounded curriculum of L2 instruction. The volume provides a comprehensive overview of the different theoretical perspectives on IC within Conversation Analysis, and moves into a discussion of conversation-analytic research findings from a variety of contexts and of their pedagogical implications.The book then presents examples of pedagogy in practice and also illustrates the potential for implementing IC in testing settings. This volume makes a valuable contribution to the growing literature on interactional competence and will be of particular interest to graduate students and researchers in applied linguistics, SLA, language education, curriculum and instruction studies, and educational linguistics.